2011
DOI: 10.1002/etc.524
|View full text |Cite
|
Sign up to set email alerts
|

Impact of coal structural heterogeneity on the nonideal sorption of organic contaminants

Abstract: Carbonaceous geosorbents (black carbon, coal, and humin/kerogen) play a primary role in the nonideal sorption (isotherm nonlinearity, hysteresis, and multiphasic kinetics) of hydrophobic organic chemicals by soils and sediments. The present study investigated the impact of coal structural heterogeneity on sorption/desorption of two model monoaromatic compounds (1,3-dichlorobenzene and 1,3-dinitrobenzene). Due to the higher degree of aromaticity and condensation, anthracite showed stronger sorption affinity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The sorption kinetic data were described by an empirical biphasic pseudo-second order model consisting of a fast sorption phase and a slow sorption phase (Shi et al, 2011;Yang et al, 2008), expressed as:…”
Section: Sorption Kineticsmentioning
confidence: 99%
“…The sorption kinetic data were described by an empirical biphasic pseudo-second order model consisting of a fast sorption phase and a slow sorption phase (Shi et al, 2011;Yang et al, 2008), expressed as:…”
Section: Sorption Kineticsmentioning
confidence: 99%
“…Morris (2013) indirectly measured the partitioning behavior of frothers methyl isobutyl carbinol (MIBC) used in the Appalachian coal industry and the results indicate a significant frother sorption to coal surfaces. A few studies on organic contaminants (PAHs, phenanthrene and methanol) indicate strong nonlinear sorption of these chemicals to coal and soot (Shimizu et al, 1998;Jonker and Koelmans, 2002;Cornelissen et al, 2006;Shi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…2, the anthracite coal originates from quartz (ICDD No: 01-089-8935) and graphite (ICDD No: 01-075-2078) crystalline phases. Quartz appearing at 37.20° is assigned as calcium silicate [12]. The main element present in anthracite is carbon.…”
Section: A X-ray Diffraction (Xrd) and X-ray Fluorescence (Xrf) Analysismentioning
confidence: 99%
“…Anthracite coal was imported from the United Kingdom, placed on the top layer of sand filter and traps large particles when the water comes in contact with the media during filtration. Shi et al, (2011) reported that anthracite contains the highest carbon content (90% to 100%) compared with lignite (60% to 75%) and hard bituminous coal (80% to 90%) [12]. Apart from having the highest carbon content, it has extremely low impurities.…”
Section: Introductionmentioning
confidence: 99%